2022
DOI: 10.15789/2220-7619-rot-1772
|View full text |Cite
|
Sign up to set email alerts
|

Role of <i>Toxoplasma gondii</i> in thyroiditis in pregnant women

Abstract: Toxoplasmosis (acute and latent) is the most prevalent parasitic infection worldwide and can be associated with some problems in pregnant women. Thyroid diseases are the most common endocrine disorders secondary to diabetes among pregnant women. Previous studies proposed a relationship between latent Toxoplasmosis (LT) and autoimmune thyroiditis diseases (AITDs). This study intended to investigate the frequency and correlation between Toxoplasmosis and AITD in pregnant women. In this cross-sectional study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…The abnormalities in the levels of FT3, FT4 and TSH hormones may increase the risks of pregnancy complications such as miscarriage, preterm delivery, placental abruption and low birth weights. The results of the current study found that seropositive IgG cases had highly elevated TPO antibodies that agrees with other studies Kankova et al 7 and Valizadeh et al, 27 . According to the effects of thyroid disorder on both mother and fetus, TPO antibodies screening should be included during pregnancy with performing the thyroid function tests and checkup by a gynecologist must be considered.…”
Section: Resultssupporting
confidence: 94%
“…The abnormalities in the levels of FT3, FT4 and TSH hormones may increase the risks of pregnancy complications such as miscarriage, preterm delivery, placental abruption and low birth weights. The results of the current study found that seropositive IgG cases had highly elevated TPO antibodies that agrees with other studies Kankova et al 7 and Valizadeh et al, 27 . According to the effects of thyroid disorder on both mother and fetus, TPO antibodies screening should be included during pregnancy with performing the thyroid function tests and checkup by a gynecologist must be considered.…”
Section: Resultssupporting
confidence: 94%
“…In the current study, we determined that there were more pregnant women with thyroid disorders than healthy thyroid function; this aligned with Valizadah et al, 45 in which T. gondii was associated with changes in thyroid hormones and TSH disturbance. In the current study, the highest rates of thyroid diseases were reported in women with seropositive Toxoplasma antibodies, rather than seronegative ones.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, out of 110 seropositive Toxoplasma women, 35(31.8%) had AITD, aligning with a study conducted by Kankova et al 46 ; specifically, Kankova et al 46 reported that 27.1% of 127 AITD women were positive for toxoplasmosis, T. gondii had an effect on thyroid production, and changes in thyroid hormone levels with highly elevated TPO antibodies were found among Toxoplasma IgG positive women compared to Toxoplasma seronegative women. Additionally, Valizada et al 45 tested 1248 pregnant women and determined that acute and latent toxoplasmosis (LT) was observed in 3.4% and 29.6% of the women, respectively; the overall frequency of thyroid diseases was 18.8%, whereas, approximately 27.9% of patients with LT had thyroid diseases. Further, 13.8% of pregnant women with LT only had AITD; a significant correlation and high elevation of TPO antibodies was also found among the seropositive Toxoplasma IgG antibody group compared to those in the Toxoplasma seronegative group.…”
Section: Discussionmentioning
confidence: 99%